Reconstituição de Belizário a partir do manuscrito P.v.v-g 117.20 - Prestes, Benjamin da Santa Cruz (2015)
The Belizário guard work with valuable information for understanding the Luso-Brazilian musical repertoire of the eighteenth century. The main music source that references the title Belizário, is in the Ducal Palace of the collection of village-lush in Portugal. Does the PVV-g 117.20 manuscript instrumental and vocal parts of the arias that were probably as part of some representations of the work in Portuguese-speaking environment. This research aims the historical context of the work, considering that it has a connection with the eighteenth century Brazil with respect to the representations and writing by at least one part of the manuscript. The musicological transcription of this manuscript became necessary, since the same physical conditions are not favorable for execution. Therefore, through the transcript, you can get the analysis of compositional schemes gallant music in an attempt to highlight structural features of arias. Keywords: Manuscript PVV-g 117.20 - musicological Transcript - Belizário.